IMPLEMENTASI AKAD QARDH DAN MURABAHAH DALAM PENGALIHAN PEMBIAYAAN (Studi Kasus pada PT. BPRS Mandiri Mitra Sukses Gresik) - Miftahul Husna; Sentot Imam Wahjono (Universitas Muhammadiyah Surabaya, 2020)
Â Researcher wanted to examine in detail the implementation of qardh and murabahah agreement in the transfer of financing (take over) conducted by PT. BPRS Mandiri Mitra Sukses Gresik Indonesia, to answer the question : How the implementation of qardh and murabahah agreement on the transfer financing practices in BPRS Mandiri Mitra Sukses Gresik ?, What is the difference of the implementation of qardh and murabahah agreement on the transfer financing practices in BPRS Mandiri Mitra Sukses Gresik ?, What are the constraints and supporting factors in the implementation of qardh and murabahah agreement ?In answering these problems used the type of qualitative research. The data collection techniques used in this study through methods of observation, interview (interview), and documentation. The data collected was compiled and analyzed using inductive thinking namely the mindset based on the facts in the field about the practice of taking over between the Conventional Financial Institution (LKK) and the bank of the Sharia Financial Institution (LKS), then linked with the qardh and murabahah theory in application take over.The result of the research that in the implementation of qardh and murabahah agreement in the transfer of financing with the purpose of taking over or transfer of financing at Bank Partners Syariah that is by the customer coming to Bank Partners Sharia to apply for taking over financing.The constraints of the implementation of qardh and murabahah agreement included the possibility of bad debts from customers and the history of customer data in SID BI that sometimes can hamper the implementation of taking over. While the supporting factors in the implementation of qardh and murabahah agreement included many fanatic customers to sharia, thus increasing the number of customers used sharia bank services, the products provided in the form of additional business capital, and ease of payment.Â Key words: utang piutang, take over, akad, the economic laws of Sharia.